Prognostic value of red cell distribution width in patients undergoing percutaneous coronary intervention: a meta-analysis - Xiaoyan Wang; Donglai Bao; Gaojiang Luo; Fuqiang Kan; Jinwei Luo; Changhao Jiang (BMJ Open)
Objective To evaluate the prognostic value of baseline red cell distribution width (RDW) in patients with coronary artery diseases (CADs) undergoing percutaneous coronary intervention (PCI) by conducting a meta-analysis.Design Systematic review and meta-analysis.Data source PubMed, Embase, Wanfang, CNKI and VIP databases were searched from their inceptions to 19 June 2019.Eligible criteria Studies investigating the value of baseline RDW for predicting all-cause mortality, cardiovascular mortality and major adverse cardiac events (MACEs) in patients with CAD undergoing PCI were included.Data extraction and synthesis Two authors independently extracted the data and evaluated the methodological quality using the Newcastle–Ottawa Scale. STATA V.12.0 software was applied to produce the forest plots using a random-effect model.Results Twelve studies (13 articles) involving 17 113 patients were included and analysed. Comparison between the highest and lowest RDW category indicated that the pooled risk ratio (RR) was 1.77 (95% CI 1.32 to 2.37) for all-cause mortality, 1.70 (95% CI 1.25 to 2.32) for cardiovascular mortality and 1.62 (95% CI 1.21 to 2.18) for MACEs. The predictive effect of elevated RDW for all-cause mortality was stronger in the subgroup of patients without anaemia (RR 4.59; 95% CI 3.07 to 6.86) than with anaemia.Conclusions This meta-analysis indicated that elevated RDW was associated with higher risk of mortality and adverse cardiac events in patients with CAD undergoing PCI. The value of elevated RDW for predicting all-cause mortality appears to be stronger in patients without anaemia. RDW may be served as a promising prognostic biomarker in patients undergoing PCI.